The Effect of Human Development Index, Ease of Doing Business, Corruption, and Distribution of ZIS Funds on Indonesia's Economic Growth - Choirul Hadi Nawawi; Al Ridhillah Sari; Achmad Vikry Hanif; Fefi Diniyati Sholihah (Indonesian Economic Review, 2022)
This study aims to determine the influence of the human development index on economic growth, ease of doing business on economic growth, corruption on economic growth, and distribution of zakat, infaq, and sedekah funds on economic growth in Indonesia. The method used in this research is quantitative with the type of associative research with the sample used is quarterly data with a 10-year observation period, so the data used is 40 sample data. The type of data used is secondary data. Data analysis using Multiple Linear Regression with an analytical tool that is SPSS. The results of the study show that: (1) the human development index has a positive and significant effect on economic growth; (2) ease of doing business has a significant positive effect on economic growth; (3) corruption has a positive and significant effect on economic growth; (4) distribution of zakat funds, infaq, sedekah has a positive and significant effect on economic growth; (5) human development index, ease of doing business, corruption, and distribution of zakat funds, infaq, sedekah have a positive and significant effect on economic growth.